NAVIGASI KOMPLEKSITAS: KAJIAN SISTEMATIS TENTANG KEPEMIMPINAN ADAPTIF DALAM MANAJEMEN KEBIJAKAN KESEHATAN - Reny Nugraheni; Dadiek Sumardianto; Wahyu Sri Astutik; Safari Hasan; Agus Sulistiawan; Dyah Novi (CV. ADIBA AISHA AMIRA, 2026)
The current healthcare system faces complex challenges that encompass ever-changing social, economic, and environmental dynamics. Traditional approaches to leadership are often inadequate to manage such complexity, necessitating a more flexible leadership model, namely adaptive leadership. This article aims to systematically review the literature discussing the role of adaptive leadership in healthcare policy management. This review was conducted by analysing 10 relevant pieces of literature, covering the implementation of adaptive leadership principles, its benefits in improving the resilience of health systems, and barriers to its application. The results show that adaptive leadership can encourage responsive decision-making, strengthen cross-sector collaboration, and increase policy innovation. However, its implementation faces obstacles such as limited training, resistance to change, and lack of resource support. This article recommends the development of adaptive leadership training and data-driven approaches to improve the effectiveness of health policy in the future.